Cycling behaviour and socioeconomic disadvantage: An investigation based on the English National Travel Survey. (October 2021) - Vidal Tortosa, Eugeni; Lovelace, Robin; Heinen, Eva; Mann, Richard P.
Abstract: One of the main challenges for policymakers aiming to promote cycling in car-oriented transport systems is how to increase social diversity among its users. The under-representation of certain groups makes it difficult to normalise cycling and distribute its benefits throughout society. Many studies have explored cycling levels in relation to age and gender, and to a lesser extent disability and ethnicity. Less attention has been paid to bicycle use related to income and other socioeconomic factors associated with disadvantage. This study aims to better understand the relationship between income and other factors of socioeconomic disadvantage and cycling behaviour. We analysed data from the English National Travel Survey to estimate the likelihood of cycling participation (if individuals cycle at all), cycling frequency ('how often' they cycle), and cycling distance ('how far' they cycle) using regression models. We found that people in lower-income households cycle less for transport, particularly for commuting, than people in higher-income households. However, no income inequalities were found for leisure cycling. In addition, low-income leisure cyclists were found to cycle more often, but higher-income leisure cyclists further. Our findings may have important policy implications. Favouring a broader focus on non-commuting cycling and subsidising cycle access and maintenance could help to diversify cycling.